Recombined flanks of the variable and joining segments of immunoglobulin genes. - Höchtl, J (1982)
The mechanism of generating immunoglobulin light chain genes by rearrangement of variable (V), joining (J), and constant (C) gene segments is still unknown. It has been discussed mostly in terms of excision and deletion of the DNA between the recombined V and J gene segments. However, the finding of DNA digests from the mouse myeloma T of a fragment (called f-T) that contains the 3' flank of a V kappa and the 5' flank of a J1 gene segment argued against a simple deletion mechanism [Steinmetz, M., Altenburger, W. & Zachau, H. G. (1980) Nucleic Acids Res. 8, 1709--1720]. The origin of fragment f-T has now been investigated by cloning and determining the sequence of the germ-line V gene segment that apparently participated in its formation. Moreover, analogous fragments containing flanking sequences were isolated from the myelomas MOPC 173 and 41 (f-173 and f-41) and studied by sequence analysis. The f fragments appear to be recombination products of V--J rearrangements reciprocal to rearranged kappa genes but, at least in the cases of f-T and f-173, not of the rearranged V genes present in the same tumor cell. This fact is best explained by a sister chromatid exchange mechanism of V--J recombination because, by this model, the rearranged V genes and the reciprocal flank recombination products would segregate into different cells during the following mitosis. The possibility is suggested that there exists in lymphocyte differentiation more than one mechanism of V--J recombination.